EVALUASI KESENJANGAN KINERJA DOESEN UNTUK MENINGKATKAN MANAJEMEN MUTU PERGURUAN TINGGI - Asep Jalaludin (Business Management Journal, 2017)
The success of a college not just depends only on how the organizational processes and implement daily activities, however routine and play activities are integrated in all components of the conditional conflict-prone organization. Increase the need of the efficiency and effectiveness bring to the requirement of the innovation efforts. It have to managed by well-plan and assured sustainability to sharpen and enhance the feasibility of-way activities, programs, and policies in the strategic management perspective (strategic management). AMIK Wahana Mandiri as one of college computer, which if it is not transforming itself in order to keep pace with changes, then it is will be eliminated out from the competition. The steps that were previously used to run mission-vision are no longer appropriate and should be replaced with a more innovative and appropriate for the achievement of the vision, mission and goals of the organization. AMIK Wahana Mandiri should examine trends which is emerging to survive, exist and continually assess the current conditions. One of important thing should consider to do is increasing the quality performance of the employee and lecturer. In the implementation of common performance gap, it is necessary for an evaluation of the performance gap in improving university management.Keyword- Evaluation, Inequality, Lecturer Performance, Quality Management, Higher Education